A hybrid methodology for analyzing the performance of induction motors with efficiency improvement by specific commercial measures - Ai, Chengliu (2020)
This paper presents a hybrid methodology to analyze the commercial measures of changing stator windings and adjusting air gap length to upgrade efficiency of typical three-phase direct-on-line induction motors with die-cast copper rotor (DCR). The calculation is carried out through combining the time-stepping and time-harmonic finite element analysis (FEA) and the circuit equivalent circuit model. Typical full-load performance of stator windings with different air gap lengths are computed by MATLAB invoking the 2D transient and eddy current field analysis in ANSYS/MAXWELL. Then, MATLAB scripts about post-processing of the FEA results are used to obtain the full-load running performance including the loss distribution and circulating current. The MATLAB scripts of circuit model built based on the FEA results is used to compare the overload and starting performance. After that, four stators with the four windings and three DCRs with different air gap of an 11 kW motor are fabricated and tested to validate the calculations. By comparing results from both calculations and measurements, it is shown that the factors of stator windings and air gap length can effectively improve the efficiency of the 11 kW DCR induction motor without the addition of extra materials. The motor with the 11/12 pitch Y-∆ series winding and 0.6 mm air gap has the best performance, in terms of efficiency, overloading capability and starting performance. Its efficiency can increase from 90% to the highest 92.35% by sole adjustment of stator winding and air gap length.